IN SITU COMPOSITE OF (Mg2Si)/Al FABRICATED BY SQUEEZE CASTING - Lus, Huseyin Murat; Ozer, Gokhan; Guler, Kerem Altug (MINERALS, METALS & MATERIALS SOC, 2012)
An in situ formed Mg2Si/Al-Si-Cu reinforced metal matrix composite fabricated by squeeze casting are investigated. It is showed that primary Mg2Si crystals are formed by adding pure Mg into hypoeutectic Al-Si-Cu alloy (A380). In order to increase castability and to obtain better properties squeeze casting technique is used. The results show that, the average size of primary Mg2Si particulates decreases from 87 mu m to21 mu m. Furthermore, the average porosity values of cast samples are significantly decreased from %8.7 to %0.5 with the application of 30 MPa pressure during solidification.
Keywords: Squeeze casting; Mg2Si/Al composites; in situ; MICROSTRUCTURE; ALUMINUM; Materials Science